Local government Weibo use and public engagement in COVID-19: A mediating role of government trust, credibility, and transparency - Chengdan, Luo; Mohd Hasan, Nurul Ain; Ahmad, Abdul Mua’ti Zamri (Human Resource Management Academic Research Society, 2023)
In recent years, local governments in China have started experimenting with social media platforms like Weibo and WeChat, among others, to communicate with the public during emergencies. Local governments' use of Weibo to disseminate information during emergencies has significantly impacted public engagement. This study proposes a model for analyzing public engagement in which local government Weibo and government trust, credibility, and transparency during the COVID-19 crisis serve as mediators. This study selected the Wuhan local government as the study control and surveyed 356 members of the Wuhan public via the Internet. The findings indicate that local government Weibo positively influences public perceptions of government trust, credibility, and transparency, thereby providing lessons for how local governments should respond to public crisis events in the era of social media